1983
DOI: 10.1104/pp.72.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of Phloem Unloading of Sucrose in Corn Roots

Abstract: The pathway of phloem unloading and the metabolism of translocated sucrose were determined in corn (Zea mays) There are several possible pathways for assimilate unloading in sink regions (Fig. 1). One possibility is that sucrose exits the phloem via either a passive, facilitated, or energy-dependent transfer step and enters the apoplast. Sucrose can then either be hydrolyzed by a cell wall invertase to hexoses which are then accumulated by hexose-specific carriers in adjacent consuming cells or sucrose can e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
88
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 11 publications
(11 reference statements)
8
88
0
2
Order By: Relevance
“…Sadler, V.R. Franceschi [1983] Plant Physiol 72: 362-367), which grow apical to the end of the phloem and must build all biomass with carbon supplied from the shoot or kernel. We derived an expression for the growthsustaining Suc flux, which is the minimum longitudinal flux that would be required to meet the carbon demands of growth in the root apical meristem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sadler, V.R. Franceschi [1983] Plant Physiol 72: 362-367), which grow apical to the end of the phloem and must build all biomass with carbon supplied from the shoot or kernel. We derived an expression for the growthsustaining Suc flux, which is the minimum longitudinal flux that would be required to meet the carbon demands of growth in the root apical meristem.…”
mentioning
confidence: 99%
“…Work by Giaquinta et al (1983) and Dick and ap Rees (1975) indicated that transport of Suc in primary maize roots is entirely symplasmic. If so, the transport characteristics would be affected by the transport capacity of plasmodesmata.…”
mentioning
confidence: 99%
“…The hydrolysis products of sucrose, fructose, and glucose, are also known to play key roles in carbohydrate movement in those plant species which employ sucrose hydrolysis between assimilate source and sink (4,8,9 , unpublished) showed that asymmetrically labeled sucrose is inverted during accumulation by isolated cotton embryos. The uptake of glucose and fructose and the effect of these sugars upon sucrose influx in cotton root and leaf discs was therefore investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrolysis products of sucrose, fructose, and glucose, are also known to play key roles in carbohydrate movement in those plant species which employ sucrose hydrolysis between assimilate source and sink (4,8,9). Hampson et al (1 1, 12) analyzed carbohydrate accumulation by excised cotton hypocotyl and concluded that cellular invertase is functionally absent in this tissue.…”
mentioning
confidence: 99%
“…24). In expanding leaves (19,26), and roots (11), a symplastic pathway has been indicated. The pathway for phloem unloading and uptake of phloem solutes into expanding cells in the elongation zone of stems has not been well characterized.…”
mentioning
confidence: 99%